Effect of Mesh Distribution on Impact Resistance Performance of Kenaf Fibre Reinforced Concrete - Muda Z.C.; Thiruchelvam S.; Syamsir A.; Sheng C.Y.; Beddu S.; Mustapha K.N.; Usman F.; Kamal N.L.M.; Alam M.A.; Birima A.H.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Concrete slabs; Concretes; Drops; Fiber reinforced materials; Hemp; Kenaf fibers; Reinforced concrete; Drop weight impact; Fibre reinforced concrete; Impact energy; Impact performance; Impact resistance performance; Mesh distributions; Projectile tests; Slab thickness; Mesh generation; crack propagation; diameter; height; impact; performance assessment; reinforced concrete; research work; size; steel; testing method; weight; Hibiscus cannabinus